2023
DOI: 10.1177/13524585231172490
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cigarette smoking on cognitive processing speed and brain atrophy in multiple sclerosis

Abstract: Background: Smoking is associated with an increased risk of multiple sclerosis (MS) and disability worsening. The relationship between smoking, cognitive processing speed, and brain atrophy remains uncertain. Objective: To quantify the impact of smoking on processing speed and brain volume in MS and to explore the longitudinal relationship between smoking and changes in processing speed. Methods: A retrospective study of MS patients who completed the processing speed test (PST) between September 2015 and March… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…An interrelation of these two factors is likely. However, whether the higher EDSS in men is driven by the longer disease duration or additionally influenced by smoking behavior, as robustly shown before, 15 20 cannot be answered by our data. Of note, persons experiencing their first clinical relapse (31.3%) were not included in this pre-relapse EDSS, which is why we refrained from calculating the EDSS difference pre- to during relapse.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…An interrelation of these two factors is likely. However, whether the higher EDSS in men is driven by the longer disease duration or additionally influenced by smoking behavior, as robustly shown before, 15 20 cannot be answered by our data. Of note, persons experiencing their first clinical relapse (31.3%) were not included in this pre-relapse EDSS, which is why we refrained from calculating the EDSS difference pre- to during relapse.…”
Section: Discussionmentioning
confidence: 53%
“… 3 , 9 Taken together, these data with poorer relapse recovery and more motor involvement in men might suggest a general effect of male sex on higher disability progression 11 indicating that additional factors must play a role. Among the latter surely are patient age, disease duration, and disease-modifying treatment (DMT), 2 , 10 , 13 but also individual and possibly gender-influenced behavioral factors, especially smoking 15 20 and obesity. 21 …”
Section: Introductionmentioning
confidence: 99%
“…Table 1 summarizes the major risk factors associated with cognitive impairment in MS, highlighting possible underlying pathophysiological and relevant references published in the last ten years. Diet Gut-brain axis Renin-angiotensin-aldosterone system [41][42][43][44] Lack of physical exercise To be determined [45,46] Smoking Increased plaque load Reduced gray matter fraction [47][48][49][50] Vitamin D deficiency…”
Section: Major Risk Factors For Cognitive Impairment In Ms Patientsmentioning
confidence: 99%
“…Regarding the smoking-cognitive impairment association, even older studies assess this negative link [48]. MRI studies in MS smokers showed a correlation between smoking, MS, and an increased plaque load, together with reduced brain parenchyma and gray matter fractions [49]. Moreover, smoking cessation showed significant improvement in the evolution of MS, slowing the rate of motor disability deterioration, equivalent to the natural MS progression in non-smokers [50].…”
Section: Lifestyle Risk Factorsmentioning
confidence: 99%